3D conformal bandpass millimeter-wave frequency selective surface with improved fields of view - H. Fernández Álvarez (Nature Portfolio, 2021)
Abstract Conventional planar frequency selective surfaces (FSSs) are characterized in the far-field region and they are sensitive to the incidence angle of impinging waves. In this paper, a spherical dome FSS is presented, aiming to provide improved angular stable bandpass filtering performance as compared to its planar counterpart when the FSS is placed in the near-field region of an antenna source. A comparison between the conformal FSS and a finite planar FSS is presented through simulations at the frequency range between 26 to 40 GHz in order to demonstrate the advantages of utilizing the conformal FSS in the near-field. The conformal FSS is 3D printed and copper electroplated, which leads to a low-cost and lightweight bandpass filter array. Placing it in the near-field region of a primary antenna can be used as radomes to realize compact high-performance mm-wave systems. The comparison between simulated and measured conformal FSS results is in good agreement. The challenges that arise when designing, manufacturing, and measuring this type of structure are reported and guidelines to overcome these are presented.